Teamwork Makes the Dream Work: Scaling Up Effective Peer Feedback in a Large-enrollment Project-based Course - Logan Paul; Alexis Peirce Caudell (Journal of Teaching and Learning with Technology)
Employers want graduates who excel in communication, collaboration, and teamwork (Dewar, 2023). But, implementing activities and assessments to support this skill development can be challenging in large-enrollment classes where the balance between the extra work it creates for faculty, and perceived value for students, must be carefully considered. This quick hit details a system, soon to be Canvas tool, for peer feedback in a large-enrollment, team-based project course. The system manages the intake and aggregation of data, and visualizes data trends across the lifecycle of the year long course. This provides the students feedback that they need to understand how their peers perceive their collaborative skills, and enables faculty to have easy access to data when having critical conversations with students based on feedback trends. In Fall 2022, 80% of students reported taking action based on  peer feedback, rising to 93% in Fall 2023. This suggests that this system can positively impact student learning and behavior when used within a comprehensive course feedback ecosystem.